Mapping recreational fishers' informal learning of scientific information using a fuzzy cognitive mapping approach to mental modelling. (26th January 2016) - Li, O.; Gray, S. A.; Sutton, S. G.
Abstract: Fisheries management benefits from improving the communication of scientific information to recreational fishers through improved compliance and greater contributions during consultation and engagement. This study uses fuzzy cognitive mapping to collect detailed, graphic information about recreational fishers' mental models as a way to improve the way scientific information is communicated to them. Fishers were given three examples of scientific information to understand the affective, cognitive and conative reactions to different types of fisheries‐related information that they often encounter, and mental models were derived based on topics they found most and least interesting. This study identifies driving variables and constraints to fishers' interest in taking up scientific information. The results suggest a message's clarity, perceived regular usefulness, good and bad emotion and investments in money and time influence fishers' interest in taking up scientific information. Fishers' initial levels of interest in a topic also significantly affect the complexity of thought processes leading to further interest in informal learning and the relative roles of the driving variables and constraints.